Differences in fatty infiltration in thigh muscles and physical function between people with and without knee osteoarthritis and similar body mass index: a cross-sectional study - Jessica B. Aily; Marcos de Noronha; Ricardo J. Ferrari; Stela M. Mattiello (BMC Musculoskeletal Disorders)
Abstract Background People with knee osteoarthritis (OA) may have more thigh intermuscular and intramuscular adipose tissue (interMAT and intraMAT, respectively) compared to those without knee OA. Literature has not considered differences in body mass index (BMI) in the context of comparing intraMAT and interMAT between individuals with and without knee OA, matched for BMI (± 1 kg/m²). This study aims to compare interMAT and intraMAT, along with physical function (including knee extension strength), between individuals with and without knee osteoarthritis, matched by BMI. Methods Participants aged ≥ 40 years with symptomatic and radiological knee OA group (grade 2 and 3 on the Kellgren and Lawrence (KL) scale) were included in the affected group, while those with no knee pain and no radiological knee OA changes were included in the unaffected group. No participants were lost to assessment, ensuring complete data analysis for all participants. We used independent t-test and mean difference (95% CI) to compare thigh intraMAT and interMAT volume, self-reported measures (WOMAC questionnaire), physical function measures, and knee extension strength between groups. Results Forty-six participants were analyzed (23 in each group). The affected group had significantly higher intraMAT compared to the unaffected group (p < 0.05), but no differences were observed for interMAT. Self-reported outcomes and physical function measures were worse in the affected group, as was knee extension strength. Conclusion People with knee OA present higher levels of intraMAT and poorer physical function compared to those without knee OA. These findings highlight the need for further research to explore the clinical significance of intraMAT and its potential impact on physical function in this population.